On the maximum of the density of the sum random variables with the unimodal distribution - Rogozin, B. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. А. Рогозин, О максимуме плотности вероятности суммы случайных величин с одновершинными распределениями B. Rogozinas, Apie atsitiktinių dydžių, turinčių vienviršūnius pasiskirstymus, sumos tikimybės tankio maksimumą